Trends and Developments in Bioinformatics in 2010: Prospects and Perspectives - Aliferis, C. F.; Alekseyenko, A. V.; Aphinyanaphongs, Y.; Brown, S.; Fenyo, D.; Fu, L.; Shen, S.; Statnikov, A.; Wang, J. (Yearbook of Medical Informatics, 2011)
To survey major developments and trends in the field of Bioinformatics in 2010 and their relationships to those of previous years, with emphasis on long-term trends, on best practices, on quality of the science of informatics, and on quality of science as a function of informatics.A critical review of articles in the literature of Bioinformatics over the past year.Our main results suggest that Bioinformatics continues to be a major catalyst for progress in Biology and Translational Medicine, as a consequence of new assaying technologies, most predominantly Next Generation Sequencing, which are changing the landscape of modern biological and medical research. These assays critically depend on bioinformatics and have led to quick growth of corresponding informatics methods development. Clinical-grade molecular signatures are proliferating at a rapid rate. However, a highly publicized incident at a prominent university showed that deficiencies in informatics methods can lead to catastrophic consequences for important scientific projects. Developing evidence-driven protocols and best practices is greatly needed given how serious are the implications for the quality of translational and basic science.Several exciting new methods have appeared over the past 18 months, that open new roads for progress in bioinformatics methods and their impact in biomedicine. At the same time, the range of open problems of great significance is extensive, ensuring the vitality of the field for many years to come.
Keywords: Bioinformatics; translational medicine; molecular profiles; high throughput assays; next generation sequencing